ISLET CELL AUTOANTIBODY PROFILE IN A MALAYSIAN TYPE-2 DIABETES MELLITUS POPULATION - P, Janisha; P, Yun Xin; N, Serene; M, Tsu Horng; N, Mei Li; L, Chun Ren (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Latent autoimmune diabetes in adults (LADA) accounts for 2-12% of all adult diabetes, where progressive islet cell failure leads to insulin deficiency. Insulin sensitivity is a major factor in the development of Type-2 diabetes mellitus (T2DM). This study aims to investigate islet cell autoantibody profile in a multi-ethnic T2DM cohort. METHODOLOGY ELISA assays of insulin antibodies, glutamic acid decarboxylase 65 (GADA65) and tyrosine phosphataserelated islet antigen 2 (IA2) (EUROIMMUN AG, Germany) were performed for 88 subjects (50 diabetes, 31 pre-diabetes and 7 healthy). Assay was performed using subjects’ sera in duplicates and absorbance was read at wavelength 405 nm using a microplate reader. Titer positivity for anti-GAD65 and anti-IA2 were defined at ≥10 IU/ml. Subsequently, subjects were categorised into good control (HbA1C <5.6%, n=8) and bad control (≥5.6%, n=80). Statistical analysis of demographic factors was performed using chi-square test and ANOVA. RESULTS Eleven anti-GAD65 positives subjects were detected, and 1 subject presented positivity for both anti-GAD65 and anti-IA2. Among them, none are healthy subjects, 2 are pre-diabetic and 9 are diabetic, reflecting a gradual increment of β-cells failure from pre-diabetic to diabetic. A higher anti-GAD65-positives was also observed in Chinese (n=6/11, 54.5%) and in females (n=8/11, 72.7%). Comparing to anti-GAD65-negatives, anti-GAD65-positive subjects tend to be older (mean=57.6 years,±10.2), with higher HbA1c (mean=7.7%,±2.1), and higher BMI (5 overweight, 45.5% and 3 obese, 27.3%). CONCLUSION Anti-GAD65-positives detected is higher (18%) compared to studies in Singapore (7%) and China (5.9%). No statistical significance was observed when comparing autoantibody profiles with demography factors probably due to the small sample size. However, the higher prevalence of β-cell failure in T2DM diagnosed individuals in Malaysia indicates the necessity to study with a larger cohort.